Senegal’s Iodine Puzzle: Iodine Status, Salt Iodization, and Dietary Iodine Sources - Rita Wegmüller; Maguette F Beye; Ndeye F Ndiaye; Volkan Cakir; Ndèye Yaga Sy; Sitor P Ndoure; Maty D Camara; Malick Anne; Nafissatou B Lo; Jessica Rigutto; Germana H Leyna; Amid Abdelnour; et al. (Current Developments in Nutrition)
Background: Iodine is vital for human health, and its deficiency is linked to severe disorders. Although salt iodization is practiced in Senegal, evidence shows declining household iodized salt coverage. Objectives: This survey assessed iodine status in nonpregnant females and examined dietary sources contributing to their iodine intake. Methods: This cross-sectional survey was conducted in 2023 and was nationally representative. Using stratified sampling, data were collected from 866 households and from 657 nonpregnant females aged 15–49 y. Median urinary iodine concentration (UIC), urinary sodium concentration, and household salt iodine concentration were analyzed, with the apportioning of iodine sources through statistical methods to estimate iodine intake from native dietary sources, iodized salt in processed foods, and iodized household salt. Results: Iodine sufficiency was observed with a median UIC of 252 μg/L, yet regional disparities exist, with some areas showing more than adequate iodine concentrations. Coverage with adequately iodized salt was low (19%), with higher availability in urban areas. Females in urban areas showed higher UICs than those in rural areas, which might be related to a higher contribution from adequately iodized salt. Processed foods, including bouillon, contributed about half to iodine intake, with household salt accounting for only a small portion (9% in urban and 5% in rural areas). Conclusions: Despite low iodized salt coverage at the household level, nonpregnant Senegalese females have adequate iodine intake due to iodine in processed foods. Effective monitoring of iodized salt used for processed foods is essential to mitigate potential excess intake whereas ensuring continued iodine sufficiency in all population groups.